THERMODYNAMICS AND PETROLOGY OF CUMMINGTONITE - Evans B.W.; Ghiorso M.S. (My University, 1995)
Natural cummingtonite encompasses virtually the entire compositional range from Mg to Fe end-member. It occurs in several metamorphic rock types, but predominantly in amphibolites and metaironstones. Most examples were produced under amphibolite-facies conditions. Cummingtonite is also a critical indicator of T, aH2O, and fO2 in silicic volcanic rocks from shallow magma chambers. The solution properties of cummingtonite reflect the entropic and enthalpic consequences of temperature-dependent, long-range ordering of Mg and Fe2+ on the M1 + M3, M2, and M4 sites, plus modest site-mismatch energies. The stability of cummingtonite in relation to other phases is discussed.